Interleukin-1 in the Response of Follicular Helper and Follicular Regulatory T Cells - Ritvo, Paul-Gydéon; Klatzmann, David (Frontiers in Immunology, 2019)
The role of Interleukin-1 on the regulation of humoral responses is poorly documented in contrast to its role on inflammation. Recent findings suggested an interleukin-1 axis in the follicular T cell control of B cell responses, implicating interleukin-1 receptors (IL-1R1 and IL-1R2) and receptor antagonists (IL-1Ra). Here, we revisit the literature on this topic and conclude that targeting the interleukin-1 pathway should be a valuable therapeutic approach in many diseases implicating an excessive production of (auto)antibodies, such as autoimmune diseases or allergy.